Expectation, Appreciation, and Public Perception to The Calisthenics Activity of Street Workout Community - Hanggoro, Hari; Kristiyanto, Agus; Doewes, Muchsin (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
The main objectives of this research are 1) What are the forms of appreciations given by the public to the calisthenics of street workout community, 2) What are the public expectations to the calisthenics of street workout community and 3) What is the public perceptions to the calisthenics of street workout community. This research was conducted at Enggal as the center of Lampung’s street workout community. This research uses descriptive qualitative method with naturalistic approach with the subject of this research are public which is in public space during sport activity. Data collection techniques such as observation, interviews, and documentation 1) The results of research to the calisthenics on street workout community are, the Community is able to provide a positive value, the public hope this community has more membership, and socialization of enhanced calisthenics, the addition of sports facilities in the public space for calisthenics. And the public expects full support from the government in terms of providing space and simplify community permissions. As well as street workout communities are able to provide an increase in the variety of exercises, contribute knowledge and building a broad concept of friendship and able to make the public maintain and improve health. 2) The public's appreciation of the calisthenics on the street workout community shows very positive things. And the public appreciates the way communities socialize with the public through official accounts in social media, and appreciate the concept of ‘Just For Fun’ in practice. The public also appreciates that the existing facilities are well maintained, and appreciate the contribution of the community in terms of events that are held, as well as full appreciation for being able to contribute to sports and public health and reduce negative activity among young people, 3) Public perceptions of the community are very good from the way people know that there are communities that introduce calisthenics sports, the public knows the street workout community as a community that uses its own weight in training and the public is able to describe the movements made in the exercise, how to do the movement correctly, able to explain aspects of ease in accessing information if you want to join the community, and knowing the community puts of affective values into practice, able to recruit all levels of public, whether from gender differences, social strata, or age groups, as well as the public knows the street workout community has held activities in introducing of calisthenics. The presence of community in the public make the public have great expectations for this community in terms of raising awareness of the sport and the public greatly appreciatesall community activities in sports or social activities, and then all appreciation and expectation are due to the positive perception of public about street workout community of all aspects